Alterations of gut microbiota in cirrhotic patients with spontaneous bacterial peritonitis: A distinctive diagnostic feature - Zhou, Zumo; Lv, Hui; Lv, Jiawen; Shi, Yongming; Huang, Heqing; Chen, Lin; Shi, Ding (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Spontaneous bacterial peritonitis (SBP) is a severe infection in cirrhotic patients that requires early diagnosis to improve the long-term outcome. Alterations in the gut microbiota have been shown to correlate with the development and progression of liver cirrhosis. However, the relationship between SBP and gut microbiota remains unknown. Methods: In this study, we applied 16S rRNA pyrosequencing of feces to ascertain possible links between the gut microbiota and SBP. We recruited 30 SBP patients, 30 decompensated cirrhotic patients without SBP (NSBP) and 30 healthy controls. Metagenomic functional prediction of bacterial taxa was achieved using PICRUSt. Results: The composition of the gut microbiota in the SBP patients differed remarkably from that in the NSBP patients and healthy individuals. The microbial richness was significantly decreased, while the diversity was increased in the SBP patients. Thirty-four bacterial taxa containing 15 species, mainly pathogens such as Klebsiella pneumoniae, Serratia marcescens and Prevotella oris, were dominant in the SBP group, while 42 bacterial taxa containing 16 species, especially beneficial species such as Faecalibacterium prausnitzii, Methanobrevibacter smithii and Lactobacillus reuteri, were enriched in the NSBP group. Notably, we found that 18 gene functions of gut microbiota were different between SBP patients and NSBP patients, which were associated with energy metabolism and functional substance metabolism. Five optimal microbial markers were determined using a random forest model, and the combination of Lactobacillus reuteri, Rothia mucilaginosa, Serratia marcescens, Ruminococcus callidus and Neisseria mucosa achieved an area under the curve (AUC) value of 0.8383 to distinguish SBP from decompensated cirrhosis. Conclusions: We described the obvious dysbiosis of gut microbiota in SBP patients and demonstrated the potential of microbial markers as noninvasive diagnostic tools for SBP at an early stage.